Turn-on fluorescent sensor for berberine chloride in aqueous solution based on dicyanodistyrylbenzene derivative. (October 2022) - Gao, Si-Yu; Huang, Han-Jun; Zhao, Ai-Juan; Traskovskis, Kaspars; Wu, Han-Chun; Chen, Zhijian; Ren, Xiang-Kui
Abstract: A novel fluorescent probe based on water-soluble dicyanodistyrylbenzene derivative (DCS-SE) has been prepared for berberine chloride (BBC) detection. The sensing performance and mechanism of DCS-SE were elucidated by photoluminescence spectra and scanning electron microscopy techniques. The experimental results reveal that DCS-SE possesses high selectivity, fast response and quantitative recognition towards BBC in aqueous solution. Moreover, due to the electrostatic interactions induced aggregation and the subsequent aggregation-induced emission effect, DCS-SE exhibits special turn-on detecting ability, with detection limit as low as 9.3 × 10 −8 M. The strategy and principle outlined in this work may be applicable to design and prepare turn-on fluorescent sensors towards various antibiotic and biomolecules. Graphical abstract: A novel turn-on mode fluorescence probe based on water-soluble dicyanodistyrylbenzene derivative (DCS-SE) was fabricated for detecting berberine chloride. Image 1 Highlights: A novel fluorescent probe based on water-soluble dicyanodistyrylbenzene derivative (DCS-SE) has been prepared for berberine chloride (BBC) detection. Due to the electrostatic interactions induced aggregation and the subsequent aggregation-induced emission effect, DCS-SE exhibits special "turn-on" detecting ability, which can avoid interfering by photobleaching, fluorescence quenchers and other external factors. The experimental results reveal that DCS-SE possesses high selective, fast and quantitative recognition towards BBC in aqueous solution, with detection limit as low as 9.3 × 10 −8 M.